Association of P53 Protein Overexpression with Clinicopathological Features of Oral Squamous Cell Carcinoma Patients in Bali - Winata, A.; Manuaba, I. B. Tjakra. W.; Sudarsa,, I. W.; Mahadewa, Tjok G. B. (BALI MEDICAL JOURNAL, 2016)
Background: Oral cancer was a major health problem with a high incidence rate worldwide. Oral Squamous Cell Carcinoma (OSCC) in Bali, ranked as the second most common cancer after cervix carcinoma. Our understanding of OSCC hasn’t yielded a satisfactory clinical outcome; therefore, further studies about the role of biomolecular markers in OSCC are still needed. One of the biomolecular markers for prognosis and predictor for OSCC that has been a topic of research to date is p53. Method: This is a cross-sectional analytical study of 36 samples to determine the correlation between p53 overexpression with age group, tumor location, tumor stage, and tumor grade in OSCC patients. Data was processed descriptive and analytical using Chi-Square/Fisher 's Exact Test methods with a significance value of p